Identifikasi Stomata Pteridophyta di Kawasan Air Terjun Parangkikis Pagerwojo Tulungagung Jawa Timur - Arbaul Fauziah (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
The aim of this study was to identifiy the stomata morphological characters of Pteridophyta in the ​​Parangkikis Pagerwojo Waterfall area, Tulungagung. The first step of stomata observation was preparation of the abaxial leaf slice. The preparation was carried out by the replica method. Stomata character studied include types and size of stomata, the number of stomata and epidermis cells, and value of the stomatal index. The result of this study showed that stomata types of Pteridophyta were polocytic and anomocytic. Of the 15 Pteridophyta species observed, the all of stomata type were polocytic, except Selaginella which had type stomata anomocytic. Stomata oval was found in Selaginella intermedia and Phymatosorus sp., slightly oval (kidney) was found in Asplenium apogamum, Dryopteris sp., Asplenium normale, Nephrolepis bisserata, Nephrolepis davallioides, Asplenium nidus, and Pteris longipinnula sp., spherical was found in Dicranopteris linearis, Cyclosorus arida, Goniophlebium percussom, and Goniophlebium manmiense, and nonconcave was found in Coniogramme fraxinea. Stomata size affected the number of stomata. If the size of the stomata was small, the number of stomata was increasing. The highest number of stomata was found in D. linearis, which was 362, while the least number of stomata was S. intermedia, which was 18. Data on the number of stomata and epidermal cells were used to determine the stomatal index. The highest stomata index was found in D. linearis, which was 22.05% and the lowest was C. fraxinea, which was 5.44 %. Keywords: Anomocytic, Parangkikis, polocytic, Pteridophyta, stomata